Impact of Telehealth on Glycemic Control in People Diagnosed with Type 2 Diabetes: A Retrospective Cohort Study - Ahmed M. Aman Allah; Waad M. Malibarey; Sarah S. Bin Baz; Hazim A. Alsalmi; Abdullah N. Alkattan; Hanan K. Attar (The Saudi Journal of Health Systems Research)
Introduction: Telehealth is a potential method for improving the quality of care for people diagnosed with type 2 diabetes (T2D). In Saudi Arabia, there is limited research on the effectiveness of telehealth for glycemic control compared to usual care. Thus, the aim of the current study was to determine the impact of telehealth on glycemic control in individuals diagnosed with T2D, with a specific focus on the examination of hemoglobin A1c (HbA1c) values. Methods: A retrospective case-control cohort study was conducted between January and August 2024 on people diagnosed with T2D who were managed at different primary healthcare centers (PHCs) in Taif, Saudi Arabia. The cohort design of the current study consisted of two groups based on the type of clinical visit: in-person (control group) and remote (study group) visits. Results: Based on the inclusion criteria for each group, 118 patients who utilized telehealth for diabetic follow-up were included in the study group, whereas the remaining subjects (N = 125) who attended PHCs for in-person diabetic follow-up were recruited into the control group. The differences in HbA1c values between the two visits (baseline and follow-up visits) in the study group and the control group were −0.52 ± 1.35 and −0.12 ± 1.10, respectively (p = 0.012). However, logistic regression revealed no significant difference in HbA1c between telehealth use and in-person clinical visits (p = 0.053). Conclusion: Telehealth was not inferior to usual care for people diagnosed with T2D and may be associated with a major improvement in HbA1c levels. These findings contribute valuable insights to the literature, and future research endeavors can build upon this foundation to further enhance the use of telehealth in maintaining glycemic control.